(untitled) (Journal of Environmental Science and Natural Resources, 2016)
An experiment was conducted at the field laboratory of Department of Environmental Science, Bangladesh Agricultural University, Mymensingh to study the textural influence on surface and subsurface soil temperatures under various conditions. The experiment consisted of four types of soil (red, sandy, clay and peat). Observations were made at three conditions viz. bare, moist and vegetation cover. Sandy soil at bare condition showed the highest surface temperature followed by peat, red and clay soils. Sand surface produced nearly 10ºC higher values than from clay soil at around midday hours. In four types of soils, the amplitude of the daily surface temperature wave decreased in the order sand > peat > red > clay at bare dry condition. In case of subsurface temperature observed at 10 cm depth, red, clay and peat soils showed insignificant differences. Soil surface temperatures of 4 types soils under moisture condition at around mid days showed similar pattern as in dry condition i.e. sand > peat > red > clay. Soil subsurface temperatures of 4 types soils under moisture condition at around mid days showed similar pattern as in surface temperature. Among three conditions, sandy soil emitted highest long wave radiation (-649.88 Wm-2) at bare condition. The long wave radiation emitted by the surface was lower when the soil was wet and has vegetation cover. Air temperature positively correlated with soil temperature. J. Environ. Sci. & Natural Resources, 8(2): 147-151 2015